DESCRIPTION OF CAREER WOMEN IN BONTOA VILLAGE, MAROS DISTRICT - Khusnul Yuliana, Asmirah; Afiif, Ahmad; Damayanti, Eka (JURNAL SIPAKALEBBI, 2023)
The first care for children lies within the family. The main responsibility of caring for children is still borne by the father or mother even though they have other activities outside the home, such as working. Caring for mothers or working women is interesting to study because of the double burden that is carried out apart from being a caregiver as well as an employee at work. This article discusses caring for career women in the Bontoa Village. The data sources in this study were 5 housewives as well as career women who have children under the age of 5 in Bontoa Village, Maros Regency. The research instrument uses an interview guide. The data analysis technique uses descriptive analysis through the stages of data reduction, data presentation, and drawing conclusions. Research results show that: (1) The parenting model applied by career women in Bontoa Village, Maros Regency, namely democratic, authoritarian, and permissive parenting. Democratic parenting by considering the rules, not imposing the will of parents which can make children depressed. Authoritarian parenting where parents pressure children to do what parents want. Permissive parenting frees children in determining their desires. (2) Career women in the Bontoa Village, Maros Regency, in carrying out their roles as caregivers and also as career women have determined priority activities. Work problems can affect the home and children or vice versa. The most important thing is to build effective communication with family so that they can actualize themselves in their respective fields of work.